2015
DOI: 10.1007/s00592-015-0763-7
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end product (AGE)-induced hepatic stellate cell activation via autophagy contributes to hepatitis C-related fibrosis

Abstract: AGEs were found to induce autophagy and activation of HSCs, which subsequently contributes to the fibrosis in CHC patients. Blocking AGE-RAGE signaling may be a promising way to alleviate fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
(38 reference statements)
2
15
0
Order By: Relevance
“…Furthermore, AGEs enhanced BMDM cells polarization into M1 macrophage with producing IL-6 and TNF-a proinflammatory cytokines and upregulating the expressions of CD11c and CD86 through activating RAGE/NF-κB pathway in mice33. In addition, AGEs has been shown to induce autophagy in some cells, such as hepatic stellate cells34, cardimyocytes35, vascular smooth muscle cells36, and endothelial cells37. Our results for the first time show that AGEs could stimulate M1 polarized macrophage by inducing autophagy.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, AGEs enhanced BMDM cells polarization into M1 macrophage with producing IL-6 and TNF-a proinflammatory cytokines and upregulating the expressions of CD11c and CD86 through activating RAGE/NF-κB pathway in mice33. In addition, AGEs has been shown to induce autophagy in some cells, such as hepatic stellate cells34, cardimyocytes35, vascular smooth muscle cells36, and endothelial cells37. Our results for the first time show that AGEs could stimulate M1 polarized macrophage by inducing autophagy.…”
Section: Discussionmentioning
confidence: 57%
“…The unfolded protein response (UPR) is a highly conserved ER stress effector pathway transmitting signal through either of protein kinase R-like ER kinase (PERK) and inositol-requiring enzyme 1 (IRE1)/X-box transcriptional factor (XBP1) pathways that link ER stress, UPR, and fibrogenic HSC activation in distinct ways: the TGFβ pathway is stimulated in the PERK-mediated, but not IRE1/XBP1-mediated, UPR during HSC activation [284286]. Advanced glycation end product (AGE)-induced HSC activation requires autophagy in HCV-related fibrosis [287]. Transient receptor potential vanilloid 4 inhibits apoptosis in rat HSC line, HSC-T6, through induction of autophagy [288].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…When the liver is injured by viral infection or hepatic toxins, HSCs receive signals secreted by damaged hepatocytes and immune cells, causing them to transdifferentiate into activated myofibroblast‐like cells. Release of lipid droplets containing retinylesters and triglyceride is a defining feature of HSC activation . In HSCs, metabolism of lipid droplets by autophagy provides cellular energy to fuel cellular activation, collagen synthesis, and secretion .…”
Section: Discussionmentioning
confidence: 99%
“…Release of lipid droplets containing retinylesters and triglyceride is a defining feature of HSC activation. [25][26][27] In HSCs, metabolism of lipid droplets by autophagy provides cellular energy to fuel cellular activation, collagen synthesis, and secretion. 28 Here, our data from primary HSCs showed that NO inhibits autophagy.…”
Section: Discussionmentioning
confidence: 99%